High intensity focused ultrasound (HIFU) for the treatment of symptomatic breast fibroadenoma. (1st January 2019) - Hahn, M.; Fugunt, R.; Schoenfisch, B.; Oberlechner, E.; Gruber, I.V.; Hoopmann, U.; Roehm, C.; Helms, G.; Taran, F.A.; Hartkopf, A.D.; Warzecha, H.; Wiesinger, B.; et al.
Abstract: Purpose: The aim of the study was to evaluate the efficacy of high intensity focused ultrasound (HIFU) in the treatment of symptomatic breast fibroadenomas (FA) after 6 and 12 months. Materials and methods: Between December 2013 and November 2014, 27 patients with histologically confirmed FA received one application of HIFU under local anesthesia (NCT02011919). Follow-up visits occurred after 6 and 12 months measuring the FA volume and clinical symptoms. A volume reduction of more than 65% was defined as success. Core needle biopsy (CNB) was offered after 12 months if indistinct residuals were visible on ultrasound (US). Results: A successful reduction in FA volume after 12 months was achieved in 24/27 patients (89%). At baseline 16 patients (59%) had pain, which was resolved in 63% (10/16). All patients were satisfied with the cosmetic related outcome. Twenty-four patients (89%) would repeat the procedure. After 12 months 21 patients with sonographically indistinct residuals underwent a CNB. There were no vital cells in 86%. Three cases showed vital cells of FA. Retrospectively possible reasons in these three cases were an insufficient treatment due to bad visibility and insufficient fixation of the FA during HIFU and/or a too short follow-up time. Conclusion: US-guided HIFU is an effective procedure and a minimally invasive alternative for the treatment of breast FA.